Acute effects of long-distance races on heart rate variability and arterial stiffness: A systematic review and meta-analysis - Calleja-Romero, A.; Vicente-Rodríguez, G.; Garatachea, N. (Journal of Sports Sciences, 2022)
This study systematically reviewed and quantified the effects of running a long-distance race (LDR) on heart rate variability (HRV) and arterial stiffness (AS). All types of races of a distance equal to or greater than a marathon (=42.2 km) were included. A total of 2,220 articles were identified, 52 were included in the qualitative analysis, and 48 were meta-analysed. The standardised mean difference pre- and post-race of various time-domain and frequency-domain indices of HRV, mean arterial blood pressure (MAP), systolic blood pressure (SBP), diastolic blood pressure (DBP) and carotid-femoral pulse wave velocity (cfPWV) was calculated. Regarding HRV, there was a significant decrease in most of the variables considered as markers of parasympathetic activity, indicating a shift of autonomic balance towards a reduced vagal tone. Regarding vascular variables, there was a significant drop in blood pressure and reduced AS. In conclusion, running an LDR seems to have a considerable acute effect on the autonomic nervous system, haemodynamics, and vascular properties. The observed effects could be categorised within the expected acute responses to long-lasting, strenuous exercise.